Presentación - Hernández L´´opez, Dinora; Amaya Velasco, Hermann Omar; Corona Fernández, Javier (BAJO EL VOLCÁN. REVISTA DEL POSGRADO DE SOCIOLOGÍA. BUAP, 2024)
Presentación BEV 10: Configuraciones de la subjetividad contemporánea